Capacitação de profissionais da saúde na detecção precoce do câncer de pele em idosos - Mendes, Ângela Valéria Tozzi de Oliveira (2020)
Introduction: Skin diseases are very common, and their diagnosis is not always made early and properly, which leads to late and sometimes ineffective treatments. This work focuses on skin cancer and the training of professionals in the Family Health Strategy (ESF) and Basic Health Units (UBS) in the municipality of Mairinque for this diagnosis. Objective: To develop, apply and evaluate a program that assists health professionals in screening for malignant skin lesions, with a primary focus on the elderly. Material and Methods: Training was performed for these professionals, through active teaching-learning methodologies, with theoretical-practical guidance on skin cancer and through the application of pre- and post-orientation questionnaires. After the questionnaires were applied, there was rotation for six seasons, each with an image of a cutaneous lesion for diagnosis. This study is prospective, descriptive, exploratory and quantitative. Results: Twenty-eight professionals participated in the training, 17 females and 11 males, aged between 26 and 63 years. Doctors performed better both in theoretical questions and in relation to images, in pre and post training, which is expected due to academic training. Dentists and nurses obtained a gain in knowledge, although small, after training mainly in relation to imaging diagnosis. The pharmaceutical professional also showed knowledge gain, but because he was the only participant in his category, the statistical data are not relevant. Conclusion: It is valuable to train health professionals in the early detection of skin cancer, since this disease is of public health interest